Membangun sistem informasi pendaftaran siswa baru di SMA Pelita Bangsa Muara Gembong secara online - Ito Riris Immasari; Istinur Alfiah (Journal of Information System, Applied, Management, Accounting and Research, 2021)
The existence of a system that is applied online can help and facilitate human work in various aspects of life so that it is easier and more effective. The implementation of the registration of prospective new students is used as the initial process of entering a new level in education. The implementation of the registration of prospective new students who have to come directly to the school to fill out the registration form is considered ineffective and inefficient. So, to make the registration process easier, it is necessary to create an online registration information system. For the analysis stage using flowcharts, activity diagrams, use case diagrams, Erd, and hierarchies for the design stage using class diagrams. With the design of a web-based system, it can simplify the process of registering new members, storing data relating to new student registrations can be stored neatly using a database and information relating to new student registration can be obtained quickly and accurately.